IMPROVEMENT ON PT FREEPORT INDONESIA (PTFI) PERFORMANCE MANAGEMENT SYSTEM - Kaisiepo, Anthonius; Welly, John (The Indonesian Journal of Business Administration, 2017)
Abstract. Performance management is a driver for organizational excellence. The success of any organization relies upon the performance of the employees, therefore employees? performance is an important consideration for businesses. The objectives of this research are to identify the challenges or barriers that facing in the implementation of performance management in PTFI, and in conjunction with that to provide the improvement recommendation. It is important to evaluate performance management practices in PTFI, to ensure performance management in PTFI is able to drives employee behavior to align with organizational goals. This research using qualitative descriptive research method. According to the results of this study, the implementation of performance management in PTFI is considered not effective, the targets set by the Company in terms of mine production and safety aspect are difficult to achieve, in addition the Company's internal work climate is not conducive. Here are problems that cause performance management at PTFI is not effective: there is no linkage between Company goals and individual goals, issues on supervisor capabilities, and performance management practices that lead to perceived injustice. To overcome the existing problems, the proposed business solution in this study is as follows: the implementation of the balanced scorecard as a measure of company performance that can translate corporate strategy, vision, and mission to the level of execution, trainings to improve supervisory skills, improvement on feedback process, and improvement on rating scale.Keyword: performance, performance management, balanced scorecard, strategy, key performance indicator, organization.